Theridion sibiricum Marusik 1988 - Marusik, Yuri M.; Koponen, Seppo (Zenodo, 2000)
Theridion sibiricum Marusik, 1988 * Material examined: 5 ♀♀, [13] 43º52'N 134º17'E, Pravaya Izvilinka Riv, 2.08.1998, YM; 13 ♀♀,[09] env.ofAnisimovka Vill, 43º10'N 132º46'E, 24- 28.07.1998, YM. COMMENTS. The first record in the province and the southernmost locality of the whole range. Earlier known from the Middle Urals [Esyunin & Efimik, 1996] to upper Kolyma and Kamchatka, to the south to Tuva and Mongolia [Marusik, 1988a; Marusik & Logunov, 1998; Logunov et al., 1998]. Within the entire range found only in screes and stony places. : Published as part of Marusik, Yuri M. & Koponen, Seppo, 2000, New data on spiders (Aranei) from the Maritime Province, Russian Far East, pp. 55-68 in Arthropoda Selecta 9 (1) on page 66, DOI: 10.5281/zenodo.822713 : {"references": ["Marusik Yu. M 1988. New species of spiders (Aranei) from the Upper Kolyma / / Zool. Zhurn. Vol. 67. No. 10. P. 1469 - 1482 [in Russian, with English summary],", "Esyunin S-L, Efimik V. F .. 1996. Catalogue of the spiders (Arach- nida, Aranaei) of the Urals. Moscow: KMK Scientific Press. 229 pp.", "Logunov D. V, Marusik Yu. M, Koponen S. 1998. A check-list of the spiders in Tuva, South Siberia with analysis of their habitat distribution / / Ber. nat-med. Verein Innsbruck. Bd. 85 P. 125 - 159."]}